Government Responsiveness in the Prevention of Spreading Covid-19: Vietnam and Indonesia in Comparison - M. Yusuf; Ady Muzwardi; Muhammad Syukri (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This study attempts to reveal the responsiveness of both Vietnam and Indonesia in anticipating the massive external shock that was Coronavirus-19. A change in external factors, such as pandemics, has challenged politicians and governments at large to be responsive in resolving problems quickly. Generally, recent research focused on reactive policies, disaster mitigation, and medical issues, while discussing government responsiveness in disease prevention is only covered in a few studies. This research uses a comparative qualitative method with an analysis period from December 2019 to the end of May 2020. The data is derived from various secondary information sources, such as research results, news, official reports, or government statements, which are interpreted through a systematic coding process to explain the phenomenon. The primary results showed that government responsiveness determines the success of handling the deadly coronavirus in pre-pandemic and current pandemic situations. A strong political will and leadership style is essential, and a solid bureaucratic apparatus in implementing policies and programs is decisive. As an authoritarian democracy, in collaboration with CDC, Vietnam was able to anticipate before the pandemic spread and succeeded in suppressing the spread after it was detected even though it had issued a blundering policy. Meanwhile, as a democratic country, Indonesia slowly responded to the outbreak by decision making where the pandemic is handled after it is detected and spread to various regions. The rulers tend to avoid the experts and growing opinions addressed to the government.